INFORMATION AND KNOWLEDGE MANAGEMENT – A STRATEGY FOR PERFORMING MEDICAL SERVICES IN THE INFORMATIONAL ERA - Adina BĂLAN (Management & Marketing)
The unprecedented incertitude existing in the health system in Romaniaimplies menaces for the system managers. The improvement of theperformance of the medical system has never been more adequate, so thatthe health system needs specific managerial strategies. Romania needs acomplete solution which could assure a performant management of themedical information in the system, and in their plans, the managers of thehealthcare organizations must include investments for the application of theinformational technologies, like the administration of medical information, ofthe health electronic file, the medical information exchange, so that themedical service be continuous and permanent from the birth until the death ofany individual. But the piece of information is only valuable to the one whoknows how to use it, where to search for it, how to choose it and finally howto use it, so that we can say the main instrument to which the manager fromthe health system may resort rapidly in order to find new solutions isinformation.